Pelatihan Pengemasan Produk Kompos Dalam Upaya Peningkatan Pendapatan Masyarakat Pasca Pandemi Covid-19 Di Dusun Telaga Kodok Kabupaten Maluku Tengah - Restia Christianty; Meiske Wenno (LPPM STIKOM Tunas Bangsa, 2022)
The goal of this activity is to provide knowledge to the Tunas Baru Farmer Group about the importance of packaging in increasing the selling value of Compost products. The approach technique used is seminars and simulations or direct exercises. It is hoped that this service will have an impact on members of the Tunas Baru farmer group in Telaga Kodok Hamlet, Central Maluku Regency, namely an increase in the demand for compost products so that group income also increases.